Penataan Pemukiman Kumuh Di Bantaran Sungai Tanggul Indah Semarang - Perdana, Bayu; , Ir. Nurhasan, MT; , Suryaning Setyowati, ST. MT (2016)
Structuring slums along the river Tanggul Indah Semarang is a structuring process to deal with the problem of settlements in urban areas at a macro level that can be regarded as an imbalance between the growth of continuous settlement "spontaneous" in various parts of the city on the one hand, and Efforts to manage the whole city in systematic on the other. Methods through observation, interviews, literature review, the data processing, the data analysis in order to provide an input and design solutional to the public the lower middle class, the which has human resources are weak, and the Oppressed peoples in the social strata, will right Reviews their needs the container activities of living a healthy, decent and dignified. The purpose of the arrangement of slums along the river Tanggul Indah is to improve the productivity of urban land with turned back (revitalization) parts of town that are not productive by bringing private entrepreneurs, beautify and freshen the atmosphere of the city, so the city will have a pride and appeal to the rating, as well as building public infrastructure such as schools, offices, and hospitals. From this final project planning process has the intention of creating a design that puts the welfare of society along alignments, taking into account the quality of a healthy environment, and maintain local knowledge Indonesian village.